2016
DOI: 10.1038/nrm.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

The regulation and functions of the nuclear RNA exosome complex

Abstract: The RNA exosome complex is the most versatile RNA-degradation machine in eukaryotes. The exosome has a central role in several aspects of RNA biogenesis, including RNA maturation and surveillance. Moreover, it is emerging as an important player in regulating the expression levels of specific mRNAs in response to environmental cues and during cell differentiation and development. Although the mechanisms by which RNA is targeted to (or escapes from) the exosome are still not fully understood, general principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
361
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(389 citation statements)
references
References 171 publications
(290 reference statements)
6
361
0
5
Order By: Relevance
“…This suggested that TARBP2 binds to pre-mRNAs and may function in the nucleus by influencing RNA processing and clearance. The major known pathway for RNA degradation in the nucleus involves the targeted destruction of incorrectly spliced transcripts by the RNA surveillance machinery (Kilchert et al, 2016). We hypothesized that TARBP2 may take advantage of this pathway by inhibiting efficient processing of its bound introns, resulting in nuclear retention and degradation of its target transcripts.…”
Section: Tarbp2 Binding Results In Increased Intron Retention and Desmentioning
confidence: 99%
“…This suggested that TARBP2 binds to pre-mRNAs and may function in the nucleus by influencing RNA processing and clearance. The major known pathway for RNA degradation in the nucleus involves the targeted destruction of incorrectly spliced transcripts by the RNA surveillance machinery (Kilchert et al, 2016). We hypothesized that TARBP2 may take advantage of this pathway by inhibiting efficient processing of its bound introns, resulting in nuclear retention and degradation of its target transcripts.…”
Section: Tarbp2 Binding Results In Increased Intron Retention and Desmentioning
confidence: 99%
“…Selective targeting has reported roles in diverse processes such as heterochromatic silencing, suppression of untimely meiosis in Schizosaccharomyces pombe, and viral defense (Harigaya et al 2006;Lee et al 2013;Aly et al 2016;Molleston et al 2016). Since targeting of RNA for degradation by the exosome based on RNA sequence elements was covered in a recent review (Kilchert et al 2016), we discuss alternative mechanisms of RNA targeting in this final section.…”
Section: Targeting Rnas To the Exosome And Associated Complexesmentioning
confidence: 99%
“…The eukaryotic RNA exosome is a conserved multisubunit protein complex that catalyzes 3 ′ -to-5 ′ processing or degradation of a vast array of different RNA substrates Kilchert et al 2016). Since its discovery as a key factor involved in 3 ′ processing of ribosomal RNAs (rRNAs) during ribosome biogenesis in budding yeast (Mitchell et al 1997), transcriptome-wide analyses in diverse eukaryotic model systems revealed that the RNA exosome contributes to the processing and/or degradation of nearly every class of RNA (Chekanova et al 2007;Gudipati et al 2012;Schneider et al 2012;Pefanis et al 2014).…”
mentioning
confidence: 99%
“…In the cytoplasm, the exosome participates in mRNA turnover and in surveillance pathways activated when ribosomes stall on aberrant mRNAs (Schaeffer et al 2011;Graille and SĂŠraphin 2012;Shoemaker and Green 2012). In the nucleus, exosome-mediated degradation also eliminates unnecessary and defective RNAs (such as tRNAs or transcripts generated from pervasive transcription) and is involved in the biogenesis of structured RNAs [such as rRNAs and sn(o)RNAs] (Butler and Mitchell 2011;Sloan et al 2012;Kilchert et al 2016). The processing of rRNA is indeed a major function of this complex, which acts both at early nucleolar stages and at late nucleoplasmic stages of rRNA biogenesis (Thomson et al 2013;Henras et al 2015;Turowski and Tollervey 2015).…”
Section: Introductionmentioning
confidence: 99%